A Survey of the Effectiveness of Prothrombin Complex Concentrates in Controlling Hemorrhage in Patients with Hemophilia and Anti-Factor VIII Antibodies - Blatt, Philip M; Ménaché, Doris; Roberts, Harold R (Thrombosis and Haemostasis, 1980)
The treatment of patients with hemophilia A and anti-Factor VIII antibodies is difficult. Between July 1977 and June 1978, a survey was carried out by an ad hoc working party of the subcommittee on Factor IX concentrates of the International Committee on Thrombosis and Hemostasis to assess the effectiveness of Prothrombin Complex Concentrates in controlling hemorrhage in these patients. The results are presented in this paper and, although subjective, support the view that these concentrates are not as effective in patients with inhibitors as Factor VIII concentrates are in patients without inhibitors.